Trends of Pathological Findings in Patients with Thyroid Diseases: A Single-center, Retrospective Study - Masooma Naseem; Sajjad Ali; Sara Qadir; Anshahrah Riaz; Abdullah Monawwer; Burhanuddin Tahir; Zehra Naseem; Zahid Mehmood (Clinical Medicine Insights: Endocrinology and Diabetes)
Background: Globally, a rising trend has been observed in the prevalence of thyroid disorders, with many demographic and geographic factors influencing its epidemiology. Nonetheless, some cases often go undetected due to the inconsistent and non-specific nature of the clinical symptoms. Therefore, we aimed to determine the trend and relationship between various pathological findings in thyroid disease patients and their demographic factors to aid clinicians in making a prompt diagnosis and treatment plan. Methods: A descriptive correlational study was conducted from January 2020 to May 2022 at Jinnah Postgraduate Medical Center, Karachi. We collected data via random sampling from 258 patients suffering from thyroid disorders. We evaluated baseline patient characteristics, along with, thyroid scan and fine needle aspiration cytology (FNAC) reports, and local thyroid gland examination findings. Results: Out of 258 participants, 192 (74.4%) were females, whereas 66 (25.6%) were males, giving a female: male ratio of 2.9: 1. On local examination, 167 (64.7%) were found to have a solitary nodule, 79 (30.6%) had multinodular goiter. Findings revealed that benign follicular lesions had the highest prevalence (35.3%). Moreover, among the cancerous growth, papillary carcinoma presented the highest cases (12.4%). Of 258 cases, 24 patients had non-surgical interventions, while most (234) had surgical interventions. Total thyroidectomy was the most common procedure opted for by 45.3% (n = 117) of the participants, followed by lobectomy 70 (27.1%), near total thyroidectomy 43 (13.2%), modified radical neck dissection 5 (1.9%). Conclusion: Our study showed that nearly all thyroid-related pathologies were more prevalent amongst females than males, with the majority having an acute to sub-acute clinical presentation. Multinodular goiter was a prominent finding indicating a greater need for screening tools and access to healthcare facilities, especially in rural areas, to allow future studies to compare provinces accurately.